Comparative evaluation of two dural closure techniques for U-shaped incisions: sealing efficacy vs. site-specific infection risk - Wang, Yu; Zhao, Chang-Zhi; Zhang, Kai-Long; Chen, Yi-Xiao; Li, Ao; Yin, Jie; Long, Fei; Wang, Qi-Hong (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to compare the outcomes of direct suturing (Method 1) and pericranium-assisted suturing (Method 2) for U-shaped dural incisions, with a specific focus on site-specific differences in cerebrospinal fluid (CSF) leak and postoperative infection.MethodsIn this retrospective cohort, 172 patients undergoing repair of U-shaped dural incisions were analyzed. Based on intraoperative feasibility, patients underwent either Method 1 (n = 94) or Method 2 (n = 78). Primary and secondary outcomes were CSF leak and postoperative infection rates, respectively. Subgroup analyses were stratified by surgical site (supratentorial vs. infratentorial).ResultsThe incidence of CSF leak was low and comparable between the two methods, regardless of surgical site (Method 1: 7.14% supratentorial vs. 7.69% infratentorial, P = 1.00; Method 2: 4.17% vs. 3.33%, P = 1.00). Re-repair rates were similarly low across all groups. However, Method 2 was associated with a significantly higher overall infection rate in the infratentorial compartment compared to supratentorial surgeries (23.33% vs. 6.25%, P = 0.039). Sub-analysis revealed this was primarily driven by a higher incidence of incision infection/delayed healing in the infratentorial group (16.67% vs. 2.08%, P = 0.028), whereas meningitis rates were comparable. Multivariable analysis confirmed the surgical site itself was not an independent risk factor for infection.ConclusionBoth direct and pericranium-assisted suturing are effective in preventing CSF leak for U-shaped dural incisions. However, the pericranium-assisted technique carries a significantly increased risk of incision-related infections in the infratentorial region. Clinical decision-making must therefore balance the reliable sealing capability of pericranium-assisted repair against its site-specific infection profile, particularly in complex posterior fossa surgeries.